Determinants of M-REITS share price in Malaysia - Mohd Arif, Md Nasir (2021)
This research was to investigates how to determine M-REITS share price in Malaysia. The identification of factors was carried out through a literature review. A variable selection process was conducted so that only independent variables that would add the most value to the analysis were put through to the analysis. 17 REITs listed on Bursa Malaysia were analysed. The data source spanned 10 years of data from 2011 to 2020; however, only 13 M-REITs data were compiled because the other 4 M-REITs were listed below ten years. The data analysis was conducted using EVIEWS Software, and the results concluded that Dividend Yield (DY) has significant with M-REITs share price while Interest Rate (IR) and Inflation Rate (IFR) has insignificant to M-REITs share price.